Development, Climate Change Adaptation, and Maladaptation: Some Econometric Evidence - Francesco Bosello; Shouro Dasgupta (Fondazione Eni Enrico Mattei (FEEM), 2015)
This paper examines the determinants of climate related disasters and attempts to estimate the presence of adaptive capacity in terms of per capita income and population density elasticities. We find evidence of adaptive capacity in a “weak” form both in terms of income and population density elasticities over our entire sample. That is, damages are in fact increasing with income and population, but less than proportionally. There is also evidence of countries improving their adaptive capacity over the long run, but of maladaptation occurring in the short run. Repeating the analysis splitting the sample by per-capita income levels, we find that higher income countries show adaptive capacity in a “strong form”, i.e. damages decrease with GDP, while lower income countries highlight exactly the opposite behavior. Finally, using Granger causality tests for panel data, we find evidence of increase in GDP per capita Granger causing climate related damages for lower income countries, but not in higher income countries.
Keywords: C19; Q54; Q56; 330; Climate Change Damages; Adaptation; Panel Granger Causality